Biochemical profiling of quality protein maize inbred lines for optimized biofuel production - Pratikshya, Mishra; Mishra, Abinash; Smruti Ranjan, Padhan; Kailash Chandra, Samal; Manasi , Dash; Dayanidhi , Mishra; Mahendra Kumar, Mohanty; Devraj , Lenka; Digbijaya , Swain (Plant Science Today, 2025)
The rising demand for sustainable energy sources has necessitated the exploration of crops with enhanced biofuel production potential. Quality Protein Maize (QPM) offers a promising alternative for biofuel research due to its unique biochemical composition and high biomass yield. This study evaluated QPM inbred lines for biofuel potential through morpho-biochemical analysis. Key morphological traits, including plant height, leaf area, stalk diameter and grain yield, were assessed. Biochemical profiling measured cellulose, hemicellulose and lignin content in stover and kernels. Initial screening identified 30 high-performing lines for further biochemical evaluation. The lignocellulosic stover biomass exhibited cellulose content ranging from 28.05 % to 37.05 %, hemicellulose from 7.06 % to 15.81 % and lignin from 20.65 % to 28.35 %. In contrast, biochemical profiling of the kernel revealed significantly higher cellulose content (65.36 % to 75.02 %), lower hemicellulose levels (1.09 % to 4.45 %) and lignin content ranging from 3.56 % to 6.07 %. Inbred lines DQL 2037 and DQL 222-1-1 exhibited significantly (p=0.05) superior mean performance for biofuel-related morphological traits. Inbred lines DQL 2159, DQL 222-1-1 and DQL 2272 exhibited significantly higher cellulose of 37.05, 35.98 and 35.53 %, respectively along with a significantly lower lignin content of 20.65, 22.25 and 22.53 % respectively in maize stover. Principal Component Analysis (PCA) and correlation matrix techniques were employed to identify key traits contributing to variability and to cluster genotypes with superior biofuel-related traits. The identification of high-performing inbred lines with favourable lignocellulosic profiles provides a strong foundation for breeding programs focused on developing maize genotypes tailored for biofuel production. This study highlights the potential of QPM inbred lines as a renewable resource for biofuel production and provides a framework for breeding strategies aimed at enhancing biofuel efficiency.